Implementasi Aplikasi Android untuk Manajemen Stok dan Penjualan Drum Bekas Menggunakan Metode Waterfall - Anis Novi Saffitri; Arief Tri Arsanto (Explore: Jurnal Sistem Informasi dan Telematika (Telekomunikasi, Multimedia dan Informatika), 2025)
In the used drum sales industry, many small and medium businesses still use conventional methods to record stock and transactions, leading to errors and inefficiencies. The purpose of this research is to create and implement an Android-based mobile application that has the capability to digitally monitor stock and sales of used drums. Needs analysis, system design, implementation with React Native and Node.js, Blackbox testing, and usability testing on 21 respondents were used as the Waterfall development method. The research results indicate that the application has a usability level of 87.2%, is capable of recording item data, monitoring the inflow and outflow of goods, and presenting real-time stock reports.It is assessed that this application is very helpful in improving the efficiency of data-driven and operational decision-making processes. In short, the application created not only functions technically but is also favored by users. This study provides a model for the development of similar applications in the future and offers a suitable digital solution for SMEs to manage the inventory and sales of used drums.